THE COMPARISON BETWEEN THE OESOPHAGEAL RESECTION AND THE RADIOTHERAPY - "K. Holakouie Naieny; K .Mohammad; K. Nasseri; A. Abasah " (Tehran University of Medical Sciences, 1989)
In this study esophageal resection and radiotherapy methods were compared in relation to the patients suffering from esophageal cancer. Three hundred and fifty-four Patients with squamous cell carcinoma of esophagus who had been hospitalized in the cancer institute of the Imam Khomeini Hospital, Tehran, during 1981-1985 were followed up through March 21st, 1987. Based on the findings, patients who had undergone esophageal resection showed higher overall survival rates. Nevertheless, considering fixed levels of some independent variables (age, grade of dysphasia and site of the tumor), the above generality is not considered valid.